'I Left My Old Self in the Training Session and Came Back With a New One': Positive Behavioural Changes Among Young Male Participants of Psychodrama Intervention Living in an Urban Slum in Bangladesh. Issue 2 (June 2023) - Fahmi, Rukhshan; Barua, Mrittika; Rizwan, Ashfique; Rahman, Arifur; Aarafat, Easir; Jabbar, Abdul; Rabbani, Atonu; Sarker, Malabika
Sociodrama and psychodrama have shown promising behavioral and attitudinal changes among men who adhere to toxic masculine attitudes and behavior. However, it is unknown whether such an approach could potentially curb the rising gender-based violence in Bangladesh. This paper presents the findings of in-depth interviews with 12 out of the 40 men in an urban slum in Dhaka who received culturally contextualized sociodrama and psychodrama interventions and 20 close female family members. Following the intervention, the narratives revealed positive behavioral and attitudinal changes in men, including developing empathy, respect towards family members and co-workers, temper management, participation in household chores, a favorable attitude towards condom use, and reduced sexual harassment and drug abuse. The findings can be used in future research and interventions to address and reduce gender-based violence against women by men.